Alternative Model for Quarks and Leptons Using Extra-Dimensional Effective Potential - Johannes V. Djoko Wirjawan (Indonesian Journal of Physics, 2002)
Assuming that the weak-isospin, particle-type (quark or lepton), color, and generation are internal quantum numbers, we may generate those quantum numbers by cloning the Dirac operator in four flat extra dimensions and trapping fermions in a harmonic-oscillator potential in the extra dimensions. Particle identification is obtained from the group representation multiplets associated with the choice of the trapping potential in the extra dimensions. The proposed model predicts the existence of unknown particles that might be considered as dark matter candidates. The interaction of the particles and the electro-weak bosonic fields which are treated as external fields will be discussed.